Pengaruh Kompensasi, Lingkungan Kerja, dan Kepuasan Kerja terhadap Kinerja Karyawan pada PT Sat Nusapersada Tbk - Kiu, Ivan Kiu Kok Quan; Saputra, Asron (LPPM Universitas Putera Batam, 2022)
For companies, the work environment is one of the most important things in a company. And with a good and well-maintained work environment, employee performance will also be better, so that they can achieve the expected company targets. Apart from the work environment, employee performance will also be supported by compensation and job satisfaction provided by the company. The sample selection of this study used a probability sampling technique using the Simple Random Sampling method. Random sampling is the taking of samples from the population which is done randomly without regard to the strata that exist in the population. The criteria in question are 230 samples are employees or employees who work at PT.Sat Nusapersada Tbk in the last 6 months, namely July to December, which are taken randomly without regard to strata. Simultaneously the variables of compensation, work environment and job satisfaction are collectively or Simultaneous have a significant effect on employee performance at PT Sat Nusapersada Tbk. Highly recommended for further research, the number of respondents should be increased, for example by taking samples using a sample of similar companies, so that the benefits of research have more impact on compensation, work and job satisfaction at the company.